A comprehensive targeted next‐generation sequencing panel for genetic diagnosis of patients with suspected inherited thrombocytopenia. Issue 4 (8th October 2018) - Johnson, Ben; Doak, Rachel; Allsup, David; Astwood, Emma; Evans, Gillian; Grimley, Charlotte; James, Beki; Myers, Bethan; Stokley, Simone; Thachil, Jecko; Wilde, Jonathan; Williams, Mike; et al.
Abstract: Background: Inherited thrombocytopenias (ITs) are a heterogeneous group of disorders characterized by low platelet counts and often disproportionate bleeding with over 30 genes currently implicated. Previously the UK‐GAPP study using whole exome sequencing (WES) identified a pathogenic variant in 19 of 47 (40%) patients of which 71% had variants in genes known to cause IT. Aims: To employ a targeted next‐generation sequencing platform to improve efficiency of diagnostic testing and reduce overall costs. Methods: We have developed an IT‐specific gene panel as a pre‐screen for patients prior to WES using the Agilent SureSelect QXT transposon‐based enrichment system. Results: Thirty‐one patients were analyzed using the panel‐based sequencing, of which; 10% (3/31) were identified with a classified pathogenic variant, 16% (5/31) were identified with a likely pathogenic variant, 51% (16/31) were identified with variants of unknown significance, and 23% (7/31) were identified with either no variant or a benign variant. Discussion and Conclusion: Although requiring further clarification of the impact of the genetic variations, the application of an IT‐specific next generation sequencing panel is an viable method of pre‐screening patients for variants in known IT‐causing genes prior to WES. With an added benefit of distinguishing IT from idiopathic thrombocytopenic purpura (ITP) and the potential to identify variants in genes known to have a predisposition to hematological malignancies, it could become a critical step in improving patient clinical management.